Cost reduction due to efficiency of consumption of the metal in the production technology improvement in the russian mechanical engineering - Streltsova D. A., Kuzjmicheva D. S. (Interactive science, 2017)
the article describes the main trends of metal consumption in engineering industry, efficient use of metals reserves and ways of reducing material costs. The need for scientific and technological potential in the Russian mechanical engineering is noted.
Keywords: технология; машиностроение; затраты; свойства материалов; cost; technology; engineering; structure; размерные связи; структура материала; потребление металла; коэффициент использования металла; properties of materials; dimensional relationships; material; metal consumption; utilization rate of the metal